MILLA A Multimodal Interactive Language Agent - CAMPBELL, NICK; KENNY, EAMONN (My University, 2014)
We describe the motivation behind, design, and implementation of MILLA, a prototype speech - to -speech English language tutoring system
eNTERFACE
PUBLISHED
Keywords: MILLA; Digital Humanities; Intelligent Content & Communications; Computer Software